The protection of local values of Szomolya village in aspect of rural development - Szögedi, Zsuzsanna (4D Journal of Landscape Architecture and Garden Art, 2006)
The aim of this research was the more effective protection of local national values, for vvhich I chose a small villagé, Szomolya, at the feet of the Bükk Mountains as a sample area. Beside dealing vvith fundamentals, natural and landscape values, I also put emphasis on examining the settlement history connections. As a result, I got to know how these fundamentals, social and historical procedures led to the development of these values. In my opinion in settlements similary small, rich in agricultural, cultural and environmental values as Szomolya - in addition to the researches of landscape values - we should alsó prepare a summary and evaluation of the privately owned values. Careful attention, several local observations, a complex evaluation system and the forming of specific tasks are needed in order to protect, restore and compose the suggestions for further development.
Keywords: Szomolya; landscape planning; settlement development; protection of values